2015
DOI: 10.7554/elife.06181
|View full text |Cite
|
Sign up to set email alerts
|

Extensive site-directed mutagenesis reveals interconnected functional units in the alkaline phosphatase active site

Abstract: Enzymes enable life by accelerating reaction rates to biological timescales. Conventional studies have focused on identifying the residues that have a direct involvement in an enzymatic reaction, but these so-called ‘catalytic residues’ are embedded in extensive interaction networks. Although fundamental to our understanding of enzyme function, evolution, and engineering, the properties of these networks have yet to be quantitatively and systematically explored. We dissected an interaction network of five resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 90 publications
1
84
0
Order By: Relevance
“…S1a and b). Whereas prior work has demonstrated that the metal content of AP in solution is two Zn 2+ ions and one Mg 2+ ion and per active site [4,18], substitution at the Mg 2+ site has previously been observed crystallographically [19]. The comparison of two previously obtained sub-2 Å resolution structures of phosphate-bound AP, one with full Mg 2+ occupancy (3TG0 from Ref.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1a and b). Whereas prior work has demonstrated that the metal content of AP in solution is two Zn 2+ ions and one Mg 2+ ion and per active site [4,18], substitution at the Mg 2+ site has previously been observed crystallographically [19]. The comparison of two previously obtained sub-2 Å resolution structures of phosphate-bound AP, one with full Mg 2+ occupancy (3TG0 from Ref.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Mg 2+ ion and its associated water network provide significantly more transition state-specific stabilization compared to Arg166, which stabilizes both the transition and ground states (Fig. 1b) [4,5,18]. The relative contributions of the Mg 2+ ion to binding affinity versus rate enhancement would thus be expected to probe how well a ligand mimics the energetics specific to AP’s transition state, so the insensitivity of vanadate but not tungstate binding affinity to loss of the Mg 2+ ion is particularly striking in the context of transition state analog behavior (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(B) k cat / K M values for phosphomonoester (Me-P) hydrolysis by WT PafA (black) and Ec AP (gray). Values are from Table 3 and ref (17). …”
Section: Discussionmentioning
confidence: 99%